MENINGKATKAN KEPUASAN PELANGGAN BIDANG USAHA PESANTREN MELALUI KUALITAS PELAYANAN DAN HARGA: INCREASING CUSTOMER SATISFACTION IN THE ISLAMIC BOARDING SCHOOL BUSINESS FIELD THROUGH SERVICE QUALITY AND PRICES - Mastur; Ziana Firdaus; Rapika Dewi; Sabrina Rahma Kamiswari; Mega Muhardi (Program Studi Ekonomi Syariah, 2025)
Realizing the economic independence of Islamic boarding schools is now the main agenda. This can be achieved by building a business that focuses on customer needs and preferences. Business continuity can also be guaranteed by continuing to improve the quality of services provided. The existence of research phenomena and gaps regarding different research results intrigued the author to test these variables at Darunnajah Fried Chicken. Quantitative research method with 100 respondents using smart PLS 4.1.0.2 data analysis. From the research days it was found that price has no effect on customer satisfaction, price has a positive and significant effect on service quality. Service quality has a positive and significant effect on customer satisfaction. Service quality is able to mediate between price and customer satisfaction. Service quality and price can influence customer satisfaction by 28.1%, while the remainder (71.9%) is influenced by variables not studied.